Effects of zinc pyrithione on biochemical parameters of the freshwater Asian clam Corbicula fluminea - Nogueira A.F. (2018)
Zinc pyrithione (ZnPT) is an organometallic biocide with bactericide, algaecide, and fungicide activity. Considering this biological activity, ZnPT has been used in anti-fouling paints, and also in human therapeutics and cosmetics, in shampoos to treat dandruff and seborrhoea. Despite its potential uses and consequent presence in the aquatic environment, the ecotoxicological effects of ZnPT are poorly understood. This work aims to characterise the effects of ZnPT in biochemical parameters of the Asian clam, one of the most invasive bivalves known for its biofouling action in hydro-dependent industries, using a classical (LC50 determination) and a biomarker-based approach (quantification of the activities of catalase, GSTs, and acetylcholinesterase, and also the muscle glycogen content). The here determined LC50-96 h for zinc pyrithione was 2.17 mg/L. ZnPT caused significant increases in the activity of catalase and of cholinesterases. These findings evidence the pro-oxidative effects caused by the metabolism of ZnPT. Despite the absence of clear effects, it is important to stress that the presence of ZnPT in the wild is usually accompanied by other pyrithiones, whose co-existence can contribute to the exertion of considerable toxic effects. © 2018 Elsevier